Research on the control and coordination of four-wheel independent driving/steering electric vehicle. (April 2017) - Jin, Lisheng; Gao, Linlin; Jiang, Yuying; Chen, Mei; Zheng, Yi; Li, Keyong
A four-wheel-independent-driving and four-wheel-independent-steering control and coordination system is proposed by combining a four-wheel-independent-steering control system and a four-wheel-independent-driving control system. The four-wheel-independent-steering control system includes a linear quadratic regulator controller that calculates four-wheel steering angles and a fuzzy logic parameter adjustor that adjusts the linear quadratic regulator control parameters based on the vehicle steering states. The four-wheel-independent-driving control system consists of three parts: a proportional–integral–derivative controller for tracking the desired vehicle speed, a sliding mode control controller, and its corresponding torque distributor for power-assisted steering. It is particularly necessary to point out that the sliding mode control controller only works when the activation condition is satisfied and the torque distribution strategy is developed on the basis of the four-wheel-independent-steering control system. Simulation studies have been conducted to evaluate the proposed system. The results show that the proposed system can improve handling stability of four-wheel-independent-driving–four-wheel-independent-steering vehicle effectively and have a strong robustness for driving on a mu-split road.